Identity crisis and cultural confrontation in jhumpa lahiri’s the namesake: a critical analysis - Yoharatnam, V.S. (University of Jaffna, 2019)
Jhumpa Lahiri was born on July 11, 1967, in London and her parents were Bengali immigrants. Her famous novel The Namesake which mirrors both the immigrant experiences in America, and the complexity of family loyalties that emphasizes all human experiences. The author depicts in this novel the delightful and happy moments as well as struggle and sufferings of the immigrants. The story entails over thirty years of Ganguli family - Ashoke and Ashima who emigrated as young adults from Calcutta to America. Their children Gogol and Sonia who were born in Unites States to face many challenges and hardships. All the diasporic experiences totally disheartened Gogol, despite his maturity and worldly wisdom. He is regarded as the epitome of the identity crisis realized by the disaporas born in foreign countries. They are vehemently grieved out of heavy nostalgic feelings, identity crisis and cultural confrontation. The main objective of this research is to analyse the identity crisis and cultural confrontation in Jhumpa Lahiri’s The Namesake. Descriptive and analytical methods will be used in this research. Data is collected from texts, different books, magazines, Journals, and articles written by scholars and critics. This research will be helpful to the readers to expand their skills in research field. In addition, this research will guide the students to develop a critical analysis of the literary works of English writers.
Keywords: Diaspora; Identity crisis; Challenges; Immigrants; Struggle